2023
DOI: 10.1007/s10750-023-05160-3
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of niche partitioning in a community of mid-trophic level epipelagic species in the North Atlantic

Abstract: According to the principles of community ecology, sympatric species may suffer a selective pressure to decrease their niche overlap through mechanisms of niche partitioning. However, there is still a gap in knowledge of the main drivers influencing niche differentiation, particularly in communities composed by small-sized and inconspicuous species. The coastal epipelagic community structure of mid-trophic level species in the Northeast Atlantic was examined using stable isotope analysis to (1) decipher intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In addition, several relationships were detected between SIA variables with both SST and Chl-a, including models involving SEAc values, highlighting the influence of oceanographic dynamics on the trophic ecology of gulls. Such isotopic composition differences are commonly linked to environmental drivers, such as SST and Chl-a concentration in species spanning from mid-to higher trophic levels within the study area [70,71]. These findings underline the significant influence of oceanographic conditions on the trophic ecology of gulls.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In addition, several relationships were detected between SIA variables with both SST and Chl-a, including models involving SEAc values, highlighting the influence of oceanographic dynamics on the trophic ecology of gulls. Such isotopic composition differences are commonly linked to environmental drivers, such as SST and Chl-a concentration in species spanning from mid-to higher trophic levels within the study area [70,71]. These findings underline the significant influence of oceanographic conditions on the trophic ecology of gulls.…”
Section: Discussionmentioning
confidence: 54%
“…In our study both δ 13 C and δ 15 N values showed a large variation over the years, in both RBC (representing the pre-laying) and plasma (reflecting incubation). We identified significant relationships between δ 15 N values and fisheries landings, particularly in the case of demersal carnivorous species (e.g., Diplodus spp., Merluccius merluccius), which are more likely to exhibit higher δ 15 N values [29,70]. These species are unlikely to be captured by gulls under natural conditions, further supporting the idea of a fisheries subsidy, particularly through discards, to their diet [37].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This study indicates a stronger ecological niche partitioning in recent years, as revealed by the relatively small (<30%) overlap of SEA B among species (Ceia et al., 2023 ; Golikov et al., 2020 ; Langton, 1982 ). All species where a decrease in niche size was observed over time adhered to this pattern, where the decrease in niche breadth was concomitant to a decrease in overlap with potential competitors (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 60%
“…This study indicates a stronger ecological niche partitioning in recent years, as revealed by the relatively small (<30%) overlap of SEA B among species (Ceia et al, 2023;Golikov et al, 2020;Langton, 1982).…”
Section: Community Structurementioning
confidence: 61%